Biocompatible polyhydroxyalkanoates/bacterial cellulose composites: Preparation, characterization, and in vitro evaluation. Issue 10 (14th June 2016) - Chiulan, Ioana; Mihaela Panaitescu, Denis; Nicoleta Frone, Adriana; Teodorescu, Mircea; Andi Nicolae, Cristian; Căşărică, Angela; Tofan, Vlad; Sălăgeanu, Aurora
Abstract: Biocompatible composites play a critical role as scaffolds in tissue engineering. Novel biocomposites made from poly(3‐hydroxybutyrate) (PHB), polyhydroxyalkanoate (PHA) and bacterial cellulose (BC) in different concentrations were prepared by solution casting and their thermal and mechanical behavior as well as biocompatibility was characterized. BC addition increased the thermal stability of the polymer matrix as evidenced by thermogravimetric analysis. The crystallinity of PHB and the crystallization temperature decreased with the addition of BC and PHA, thus increasing the processing window. BC in small concentration determined an increase in the mechanical properties due to a concerted action of PHA and filler. Good cells attachment and proliferation were observed for all the biocomposites. By the addition of PHA (more hydrophobic than the matrix) and various amounts of BC (highly hydrophilic), surface properties and cell attachment can be controlled. Cytocompatibility studies using L929 cell line revealed that this material is suitable for biomedical applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2576–2584, 2016.